Genetic diversity and population differentiation in the yellow drum Nibea albiflora along the coast of the China Sea. Issue 4 (21st April 2017) - Xu, Dongdong; Lou, Bao; Zhou, Wei; Chen, Ruiyi; Zhan, Wei; Liu, Feng
ABSTRACT: Nibea albiflora (yellow drum) is an important seafood fish species in East Asia. We explored the population genetic variation of N. albiflora along the coastal waters of the China Sea using microsatellite markers to facilitate a selective breeding programme that is undertaken in China. A total of 256 alleles were detected at 12 loci in four wild populations. A high level of genetic diversity was observed with the mean number of alleles and the observed and expected heterozygosity in each population ranging from 7.917 to 14.083, 0.701 to 0.764 and 0.765 to 0.841, respectively. Pairwise fixation index (FST ) analysis indicated significant but weak genetic differentiation among populations from four localities (FST  = 0.030, P  < 0.01), which was also confirmed by analysis of molecular variance (AMOVA). Significant genetic differentiation was detected between Ningde and the other populations (FST  = 0.047–0.056, P  < 0.01). Structure analysis suggested that N. albiflora within the examined range might be composed of two stocks. The data of the present study revealed high genetic diversity and low genetic differentiation among the N. albiflora populations along the coast of the China Sea. This baseline information could be valuable for future selective breeding programmes of N. albiflora .